Field Performance of a Self-Limiting, Genetically Engineered Fall Armyworm for Biological Pest Management - Reavey, Catherine E.; Domingues, Felipe A.; Ercit, Kyla; Pinto, Ricardo L.; Naish, Neil; Yadav, Mayur; Frazon, Tamires; Cabala, Katarzyna; Sulston, Edward; Pickl-Herk, Angela; Edwards, Matt; Miraldo, Leonardo L.; et al. (Frontiers in Agronomy, 2025)
IntroductionThe fall armyworm is one of the most globally significant agricultural pests, damaging corn, sorghum and other crops central to food production. It has developed resistance to several classes of chemical insecticides and, more recently, insect-resistant ‘Bt’ biotech corn varieties. As Bt varieties constitute the great majority of corn acreage in Brazil, proactive resistance management strategies are required to protect the durability of insecticidal efficacy of those cultivars. Previously, we reported on the development of a ‘self-limiting’ fall armyworm strain, called OX5382G, which – after release in the field – is engineered to suppress populations of fall armyworm and manage resistance to Bt crops in treated populations of this pest.MethodsHere, we build on this work by carrying out contained studies to empirically assess the pest suppression and resistance management benefits of releasing OX5382G males. We also report on the first open field releases of the OX5382G self-limiting strain in Brazil. Following commercial biosafety approval of this strain by Brazilian government regulators, deployment-relevant OX5382G male performance was then assessed in larger, operational trials in Brazil.ResultsPest suppression and resistance management benefits were demonstrated in contained studies. In the first open field releases, OX5382G males showed comparable performance with wild-type counterparts in terms of dispersal and mating ability. In the subsequent larger, farm-scale trials in Brazil, OX5382G mated effectively in the field and we demonstrated that relatively modest release rates can achieve over-flooding ratios expected to exert suppression and/or resistance management.DiscussionAll assessments to date suggest that self-limiting fall armyworm is a promising future tool for managing fall armyworm and extending the durability of Bt crops’ effectiveness against damaging lepidopteran pests.